Clean heating during winter season in Northern China: A review. (October 2021) - Zhang, Zongxi; Zhou, Yuguang; Zhao, Nan; Li, Huan; Tohniyaz, Bahargul; Mperejekumana, Philbert; Hong, Quan; Wu, Rucong; Li, Gang; Sultan, Muhammad; Zayan, Ali Mohammed Ibrahim; Cao, Jinxin; et al.
Abstract: Previous researchers found that bulk coal combustion for heating was considered as one of the most important sources of air pollution, and the replacement of coal combustion resulted in significant air quality improvement, health benefits and the reduction of CO2 emission. The clean heating forms an essential part of the energy revolution, thereby significantly influencing the rural lifestyle. The pilot program for clean heating has been launched recently. However, various challenges have remained which cannot be ignored. This study critically reviews the implications, research situation, technology, and methods associated with clean heating during winter season in Northern China. The status, technical routes, and various clean heating technologies in Northern China was introduced. The authors analyzed the advantages, disadvantages, and economics of various heating systems/methods, such as the air-source heat pumps, electric heating system, wall-mounted natural gas heater system, biomass pyrolysis cogeneration clean heating. The environmental benefits of clean heating options during winter in Northern China were evaluated based on the extensive analysis. The suggestions were presented regarding the promotion of clean heating technology. Graphical abstract: Image 1 Highlights: Current status of clean heating during the winter in Northern China was introduced. Economic and restriction of clean heating technologies adopted in Northern China was analyzed. Prospective and challenges faced during the promotion of clean heating in Northern China was proposed. Suggestions were presented regarding the promotion of clean heating technology in Northern China.